Prospects for the Study of Evolution in the Deep Biosphere - Biddle, Jennifer F.; Sylvan, Jason B.; Brazelton, William J.; Tully, Benjamin J.; Edwards, Katrina; Moyer, Craig L.; Heidelberg, John F.; Nelson, William C. (Frontiers in Microbiology, 2012)
Since the days of Darwin, scientists have used the framework of the theory of evolution to explore the interconnectedness of life on Earth and adaptation of organisms to the ever-changing environment. The advent of molecular biology has advanced and accelerated the study of evolution by allowing direct examination of the genetic material that ultimately determines the phenotypes upon which selection acts. The study of evolution has been furthered through examination of microbial evolution, with large population numbers, short generation times and easily extractable DNA. Such work has spawned the study of microbial biogeography, with the realization that concepts developed in population genetics may be applicable to microbial genomes (Manhes et al. 2011, Martiny et al. 2006). Microbial biogeography and adaptation has been examined in many different environments. Here we argue that the deep biosphere is a unique environment for the study of evolution and list specific factors that can be considered and where the studies may be performed. This publication is the result of the NSF-funded Center for Dark Energy Biosphere Investigations (C-DEBI) theme team on Evolution (www.darkenergybiosphere.org).